1976
DOI: 10.1103/physrevb.14.632
|View full text |Cite
|
Sign up to set email alerts
|

Optical investigations of the undulation spectrum of GaP:N:Zn

Abstract: The undulation spectrum occurs in the luminescence of Gap when it is doped with the isoelectronic trap, nitrogen, and an acceptor -in the present case Zn. A broad emission band is observed which extends about 20 meV below the nitrogen bound-exciton energy EA and contains regular undulations. We show that the luminescence originates from the decay of excitons bound to N-Zn pairs of up to 50-A separation, and that the undulatory behavior is a result of averaging the numbers of equivalent sites in the pair-separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…23 A compared to 1. 25 A for Zn which allows doping higher than lo1' 0111-3 providing very efficient LED while Na has a radius of 1.54 A. For I< whose covalent radius is close to 2.03 A it is not surprising that its solubility remains very small even if the diffusion is made at 750 "C in a sealed tube with a K,Te source.…”
Section: Resultsmentioning
confidence: 99%
“…23 A compared to 1. 25 A for Zn which allows doping higher than lo1' 0111-3 providing very efficient LED while Na has a radius of 1.54 A. For I< whose covalent radius is close to 2.03 A it is not surprising that its solubility remains very small even if the diffusion is made at 750 "C in a sealed tube with a K,Te source.…”
Section: Resultsmentioning
confidence: 99%
“…In GaP the "undulation spectrum" l) 85X, 38041 Grenoble Cbdex, France. relative to isoelectronic centres seems to have the same physical origin [6]. I n fact, when the impurity concentration is high enough, formation of impurity clusters dominates the properties of the material.…”
Section: Introductionmentioning
confidence: 88%
“…A more careful analysis suggests that we must consider the interaction of three or more neutral acceptors rather than only a n isolated pair. SW [6] showed that these interactions result in a broadening of the discrete line corresponding to an isolated pair. Thus the overlap of the discrete lines gives a smooth shape t o the spectra.…”
Section: Theoretical Bandshapementioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is well known, and has been observed in Gal? [15] and also for all the acceptors in ZnTe [16, 171. In fact, when the acceptor concentration increases, the mean distance between acceptor sites decreases, and so bound excitons are delocalized on several interacting When N , increases, the peak energy shifts to higher energies (Fig. 2, curves b and c).…”
Section: As-grown and Annealed Cdtementioning
confidence: 99%